Exploring coordinated development and its driving factors between carbon emission and ecosystem health in the southern hilly and mountainous region of China - Qu, Hongjiao; You, Chang; Wang, Weiyin; Guo, Luo (Frontiers in Environmental Science, 2023)
Achieving "carbon neutrality" is an inevitable requirement for tackling global warming.As one of the national ecological barriers, the southern hilly and mountainous region (SHMR) shoulder the important mission of taking the lead in achieving "carbon peak" and "carbon neutrality". Thus, it has important scientific significance to explore and analyze how to coordinate ecological development under the background of "double carbon action", and it is a key step to ensure that the region achieves synergistic development of promoting economic development and improving ecosystem health.Therefore, in this study, we aimed to address these gaps by adopting a refined grid scale of 10km×10km to explore the spatial-temporal distribution characteristics of carbon emissions and ecosystem health. Additionally, we established a coupling coordination model of carbon emissions intensity (CEI) and ecosystem health index (EHI) to assess the impact of natural and socio-economic factors on the coupling coordination degree (CCD) in different regions. Our findings are as follows: (1) In the SHMR region, the EHI exhibited a progressive development trend, with spatially increasing values from the south to the north. (2) The spatial discrepancy in CEI has been on the rise, which assumed an increase of 4.69 times, and with an increasingly pronounced pattern of spatial imbalance. Carbon emissions tend to concentrate more in the eastern and northern areas, while they are comparatively lower in the western and southern regions.(3) The R 2 of geographical weighted regression model (GWR) is all above 0.8, and the CCD between CEI and EHI demonstrated a positive developmental state. However, most regions still displayed an imbalanced development, albeit with a slight increase in areas exhibiting a more balanced development state. (4) The driving forces of natural and socio-economic factors had a dual-factor and non-linear enhancement effect on the CCD. The influence of natural factors on CCD has gradually diminished, whereas the influence of socio-economic factors has progressively strengthened.